Soil physico-chemical properties as influenced by the integrated nutrient management under sapota (Manilkara zapota L.P. Royen) based agroforestry system - AMLANI, M.H.; PRAJAPATI, V.M.; TANDEL, M.B.; PATEL, D.P.; BEHERA, L.K.; GARDE, Y. A.; SHRIVASTAVA, P.K. (Journal of Soil and Water Conservation, 2025)
The present trial was carried out with an objective to study the impact of integrated nutrient management on physico-chemical properties of soil. For the trial, GAT 5 variety of tomato was intercropped under sapota based agroforestry system and open condition during Late Rabi and Late Kharif seasons of 2022- 23. The trial was framed with twelve different treatments comprised of combinations of biocompost, vermicompost, farm yard manure, three different types of novel, biofertilizers and chemical fertilizer in various proportions under sapota plantation and in open condition with Randomized Block Design consisting of three replications. Soil physico-chemical properties viz., bulk density, porosity, water holding capacity, electrical conductivity and organic carbon were varied significantly among different treatments. The improved physical parameters such as bulk density (1.29 g/cc) was registered in treatment Natural Farming + 5 ml/ litre (Each of Azotobacter, KMB, PSB), whereas maximum porosity of soil (51.76%) was noted in Natural Farming treatment and water holding capacity (45.34%) of soil registered in Natural Farming + Novel Prime treatment. Similarly, chemical parameters of soil such as electrical conductivity (0.49 dSm-1) was recorded maximum in treatment 50% RDN through Neem coated urea + 50% RDN through Vermicompost whereas soil organic carbon content of soil (0.75%) was recorded maximum in treatment 50% RDN through Neem coated urea + 50% RDN through FYM as well as in Natural Farming treatment. Overall result confirms that there is improvement in physico- chemical properties of soil under sapota based agroforestry system as compared to open condition.